Correlation Between Types of Bacteria with Pathology Examination of Chorioamnion from Preterm Birth - Fita Drisma (Indonesian Journal of Obstetrics and Gynecology, 2012)
Objective: To determine whether there is a correlation between the types of bacteria found in amniotic membrane and intrauterine infection causing preterm delivery. Method: This was an experimental study. We studied the amniotic membrane from patients undergoing spontaneous preterm delivery, both with premature rupture of membrane and intact membrane in Dr. Hasan Sadikin Hospital and some district Hospitals around Dr. Hasan Sadikin Hospital that fulfill the inclusions and exclusion criterias. Experiments were performed in Prodia Laboratory and Pathology Department of Dr. Hasan Sadikin Hospital. The amniotic membrane was prepared in Brain Heart Infusion Broth (BHI) and Formalin. The sample prepared in BHI was then transported to the laboratory and cultured for bacteria within 24 hours after the sample was taken, and the other sample prepared in formalin was made into tissue blocks and stained with hematoxylin and eosin. Afterwards, we counted the polymorph nuclear cells and if there were more than 4 cells in view, we concluded that there was an intrauterine infection. Result: Types of bacteria and intrauterine infection found in both groups showed a significant difference (p=0.002) between the groups with PROM and the group with intact amniotic membrane. The most bacteria found in preterm delivery with amnion membrane intact was Eschericia coli (33.3%) and Streptococcus alfa hemolytic (33.3%) in premature rupture of the membrane. Based on Rank Spearman Correlation test shows a significant (p<0.05) positive correlation between intrauterine infection with preterm delivery with amniotic membrane intact and premature rupture of the membrane. Conclusion: There is a correlation between types of bacteria invading the amniotic membrane causing intrauterine infection that initiates preterm delivery. [Indones J Obstet Gynecol 2012; 36-2: 71-4] Keywords: amniotic membrane, bacteria, intrauterine infection, preterm delivery